1995
DOI: 10.1016/0375-9601(95)00233-s
|View full text |Cite
|
Sign up to set email alerts
|

Doubly discrete Lagrangian systems related to the Hirota and sine-Gordon equation

Abstract: We extend the action for evolution equations of KdV and MKdV type which was derived in NC] to the case of not periodic, but only equivariant phase space variables, introduced in FV2]. The di erence of these variables may be interpreted as reduced phase space variables via a Marsden-Weinstein reduction where the monodromies play the role of the momentum map. As an example we obtain the doubly discrete sine-Gordon equation and the Hirota equation and the corresponding symplectic structures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…where we have assumed that one can solve v n+p+q uniquely from equation (9). For example, the (3, −2)-reduction is depicted in Figure 1.…”
Section: (Q −P) Reductions Of Lattice Equationsmentioning
confidence: 99%
“…where we have assumed that one can solve v n+p+q uniquely from equation (9). For example, the (3, −2)-reduction is depicted in Figure 1.…”
Section: (Q −P) Reductions Of Lattice Equationsmentioning
confidence: 99%
“…, n − 1, and x n = F(x) (8) is a Poisson map. By now, many authors have studied similar problems from the point of view of cluster algebras [9,14], r-matrix approach [19], using three leg forms for ( p, p) reductions of maps in the ABS list [2], by considering symplectic structures [16] and many other [3,4,7,8,15,20,23,25,26].…”
Section: Equivalently If For Any Two Functionsmentioning
confidence: 99%
“…Lemma 1. Suppose that M : R n → R n , x → x is a map of the form (7) and (8) where F(x) = φ(y 1 , y 2 , . .…”
Section: Equivalently If For Any Two Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrable lattice systems of the above type had been thoroughly discussed e.g. in [BRST,NCP,S,V,FV2,CN,EK]) In [EK] it was shown that it is possible to derive the above equation as an equation of motion from an explicitly given action. Moreover -using covariant phase space techniques -it is possible to derive the symplectic structure belonging to the above model via variation of this action.…”
Section: Introductionmentioning
confidence: 99%